Repositórios digitais para informações culturais no Brasil : uma análise a partir da curadoria digital - Souza, Jordan Antonio de (2023)
The constant advances in digital technologies in contemporary times show that the use of the internet, whether for convenience or necessity, continues to gain more and more importance, remaining one of the main tools for communication and access to information. In this scenario, the different types of Digital Repositories available on the web play a significant role in enabling the dissemination and access to knowledge. When combined with the contributions that Digital Curation techniques can offer, these repositories can achieve greater visibility and reliability. Therefore, the problem investigated in this research is the use of Digital Repositories as instruments for preservation, dissemination and access to scientific and cultural information, considering the organizational options used. The main objective is to analyze the organization of information in Digital Repositories, especially those related to cultural information, considering the possible contributions of Digital Curation in the development, structuring, organization, recovery, preservation and other arrangements that enable the dissemination of information about culture. The theoretical foundation used to support the research covers publications that present concepts, elements, and applications of models related to Digital Repositories, Digital Curation, Culture and Cultural Information. The most relevant publications to the research topic were selected, allowing the state of the art to be verified. The development of this work is based on resources from documentary, bibliographic and exploratory research, relevant to achieving the proposed objectives. These methods enable a qualitative approach to data interpretation, also using the content analysis method, and functionalist and structuralist interpretation methods to corroborate the analysis of digital repositories. In this way, the research investigates digital repositories that deal with cultural information, considering the contributions that Digital Curation can offer in the aspects of preservation, dissemination and access to cultural content.